Ethics and ontology: Hans Jonas’ looking for the imperative of responsibility in the age of technology - Bacevičiūtė, Danutė (Religija ir kultūra, 2013)
The article deals with the problem of relationship between ethics and ontology in Hans Jonas’ search for the imperative of responsibility in the age of technology. One can see the relationship between ontology and ethics as problematical not only because of the traditional distinction between the theoretical and practical reason, but also because of the Martin Heidegger’s attempt to return to fundamental ontology in terms of the henomenological Dasein analysis which differently incorporates the practical dimension. Jonas follows Heidegger when he notices that the nature of human action has changed in the technological age. The author of the article maintains that the phenomenon of technology is constitutive for Jonas’ formula of the responsibility imperative. Furthermore, the relationship between ontology and ethics is confirmed by Jonas’ orientation towards the real or genuine ethics (wirkliche Ethik), as well as towards the ontological grounding of ethics. However, Jonas’ stand against anonymity of Heidegger’s being, which can annul the ethical dimension and make one to resign facing necessity is also stressed. The article concludes that avoiding this anonymity Jonas declares the teleological notion of being as a kind of neo-Aristotelianism. The article questions whether the Aristotelian teleology can offer an adequate counterbalance for the dominant anonymity of modern technology. Maybe ethics should remain as an alternative to ontology instead of seeking for its ontological grounding.